Multifinality of peer victimization: maladjustment patterns and transitions from early to mid-adolescence - Kretschmer, Tina; Barker, Edward D.; Dijkstra, Jan Kornelis; Oldehinkel, Albertine J.; Veenstra, René (European Child & Adolescent Psychiatry, 2015)
Peer victimization is a common and pervasive experience in childhood and adolescence and is associated with various maladjustment symptoms, including internalizing, externalizing, and somatic problems. This variety suggests that peer victimization is multifinal where exposure to the same risk leads to different outcomes. However, very little is known about the relative likelihood of each form of maladjustment. We used a latent profile approach to capture multiple possible outcomes and examined prediction by peer victimization. We also examined the role of peer victimization with regard to stability and change in maladjustment. Maladjustment symptoms and peer victimization were assessed from the participants of the large cohort study TRacking Adolescents’ Individual Lives Survey in early and mid-adolescence. Latent profile and latent transition analyses were conducted to examine associations between victimization and maladjustment profile and to test the role of victimization in maladjustment profile transitions. Four maladjustment profiles were identified for early adolescence (Low, Internalizing, Externalizing, Comorbid) and three profiles (Low, Internalizing, Externalizing) were identified for mid-adolescence. Internalizing problems were more likely in victimized adolescents than low symptom levels or externalizing problems. Victimized adolescents were at greater risk to develop internalizing problems between early and mid-adolescence than non-victimized adolescents. Peer victimization is multifinal mostly when outcomes are examined separately. If multiple outcomes are tested simultaneously, internalizing problems seem to be the most likely outcome
CRIS-Team Scopus Importer:2025-03-19
Keywords: Externalizing; Internalizing; Latent profiles; Latent transition; Multifinality; Peer victimization